A process for change: The safe system approach and Vision Zero - Schell, William J.; Ward, Nicholas J. (Frontiers in Future Transportation, 2022)
To support the vision of zero traffic fatalities (and serious injuries), there is growing interest in the safe system approach within the United States. For many stakeholder organizations, establishing the safe system approach to reach Vision Zero represents a fundamental change in how they (1) perceive the road transport system, (2) interpret their role in that system, (3) operate with other system elements (stakeholder organizations), and (4) define a vision of success for the system. This requires a transformative change that requires structured preparation and deliberate management of the change process. This paper presents a perspective on a process to initiate and manage this change.